Executive Networks and Firm Policies: Evidence from the Random Assignment of MBA Peers - Shue, Kelly (Review of Financial Studies, 2013)
[Using the historical random assignment of MBA students to sections at Harvard Business School (HBS), I explore how executive peer networks can affect managerial decision making. Within an HBS class, firm outcomes are significantly more similar among graduates from the same section than among graduates from different sections, with the strongest effects in executive compensation and acquisitions strategy. I demonstrate the role of ongoing social interactions by showing that peer effects are more than twice as strong in the year following staggered alumni reunions. Supplementary tests suggest that peer influence can operate in ways that do not contribute to firm productivity.]